Sustainable Green University: Waste Auditing, German Jordanian University as a Case Study - Hindiyeh, Muna; Jaradat, Mustafa; Albatayneh, Aiman; Alabdellat, Batool; Al-Mitwali, Yazan; Hammad, Bashar (Frontiers in Built Environment, 2022)
In order to get on the path of sustainable development as a society as a whole, a great transformation is required. Universities are embedded in society and networked with it through a variety of forms of in-teraction; they influence social discourses and often have a decisive influence on them. As educational institutions, universities have to take a critical stance on the state of our earth and actively fulfill their responsibility. The German Jordanian University (GJU) like any other university produce both solid waste and hazardous waste. Conducting a waste audit was done to identify the waste streams and the opportunities for reinforcing waste reducing, recycling and composting whereas enhancing the compre-hensive sustainability of a waste management program. The results showed that an average of 2,500 kg of waste was produced per week. The composition of the waste generated at GJU main campus was 1,051 kg (41%) for paper and cardboard, 875 kg (35%) for plastics, 325 kg (13%) for bio-waste, and 275 kg other wastes. The performed UI GreenMetric showed a high potential in the programs to reduce the use of paper and plastic on campus as well as in the treatment of toxic waste with a score of 75 points. The results of this study indicate that there is a high potential in the recycling program for the university waste, organic and inorganic waste treatment, and sewage disposal. The results for these indi-cators were moderate, score of 75 points out of 300 points. Thus, more focus and actions should be placed on these indicators to enhance sustainable green campus.